Quadratic pairs in characteristic 2 and the Witt cancellation theorem - Mohamed Abdou Elomary (International Journal of Mathematics and Mathematical Sciences)
We define the orthogonal sum of quadratic pairs and we show that there is no Witt cancellation theorem for this operation in characteristic 2.